The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.2042-3306.1992.tb02839.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk and water intakes of foals sucking grazing mares

Abstract: Summary Intakes of milk and milk nutrients were determined for 8 foals at 11–18 days of age and for 10 foals at 30–44 days and 60–74 days of age while sucking grazing mares. Water intakes (sources other than milk) of the foals were determined at 30–44 days and 60–74 days of age. Five of the 10 mares were fed a protein supplement (24% crude protein) in addition to grazing during the stud season. The protein supplement did not influence foal intakes of milk and milk nutrients, milk composition, weight gains of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
7
23
1
3
Order By: Relevance
“…The same happened, at least until the 5th lactation month, for the NPN index calculated with reference to non-casein N content (NPN × 100/NCN), whose values varied between 17.74% (d 4) and 24.28% (d 150). The NPN index trend is completely in accordance with what was reported by Neseni et al [32], Martin et al [29] and Mariani et al [28]. Other authors, instead, observed very limited variations, increasing [10,14,33], or having rather irregular variations [41].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The same happened, at least until the 5th lactation month, for the NPN index calculated with reference to non-casein N content (NPN × 100/NCN), whose values varied between 17.74% (d 4) and 24.28% (d 150). The NPN index trend is completely in accordance with what was reported by Neseni et al [32], Martin et al [29] and Mariani et al [28]. Other authors, instead, observed very limited variations, increasing [10,14,33], or having rather irregular variations [41].…”
Section: Discussionsupporting
confidence: 90%
“…Such variations are in agreement with the observations of Ullrey et al [42], Burns et al [8] and Mariani et al [28]. Analogous indications, but relative only to the first 2 months of lactation, have also been reported by Oftedal et al [34], Doreau et al [14] and Martin et al [29], while Doreau et al [15], in the same period, did not find any considerable variation.…”
Section: Gross Energysupporting
confidence: 92%
See 1 more Smart Citation
“…Non-protein N decrease of the milk from the early lactation phases (day 4 to day 60) was in substantial agreement with those observed by other authors (Doreau et al 1990;Martin et al 1992;Csapó-Kiss et al 1995). Other studies found no significant variations (Oftedal et al 1983;Oftedal and Jenness 1988) or an irregular trend.…”
Section: Discussion Nitrogen Composition Of Mare's Milksupporting
confidence: 82%
“…The NPN index trend agrees with what reported by Neseni et al (1958), Martin et al (1992) and Mariani et al (1993). Other authors observed very limited variations, increasing (Oftedal and Jenness 1988;Doreau et al 1990;Csapó-Kiss et al 1995), or having rather irregular variations (Storch 1985).…”
Section: Nitrogen Distributionsupporting
confidence: 82%